DAMPAK DIGITAL MARKETING TERHADAP KINERJA UMKM DI PALEMBANG - Hartiningsih Apriliza; Sulastri, Sulastri; Rosa, Aslamia (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research aims to investigate the impact of digital marketing on the performance of MSMEs in Palembang, specifically at Palembang Indah Mall (PIM).Methods: The sample in this study consisted of 91 SMESs, which were obtained through a simple random sampling technique. The data collection method involves distributing questionnaires to MSMEs, and the data are then processed using Structural Equation Modeling (SEM).Results: The study's findings indicate that digital literacy has no significant positive impact on the performance of MSMEs. However, e-commerce and digital support facilities have a considerable positive impact on the performance of MSMEs. Meanwhile, the effectiveness of digital marketing can mediate the relationship between digital literacy and MSME performance. Then, the effectiveness of digital marketing can also mediate the relationship between e-commerce and MSME performance. The effectiveness of digital marketing can mediate the relationship between supporting facilities and MSME performance. The effectiveness of digital marketing has a positive and significant impact on the performance of MSMEs. Keywords: SMEs, Digital Literacy, E-commerce, Digital Support Facilities, Effectiveness of Digital Marketing, Performance of SMEs.